Utilising improvement science methods to optimise medication reconciliation. Issue 4 (11th February 2011) - White, Christine M; Schoettker, Pamela J; Conway, Patrick H; Geiser, Maria; Olivea, Jason; Pruett, Raymond; Kotagal, Uma R
Abstract : Background: In 2005, The Joint Commission included medication reconciliation as a National Patient Safety Goal to reduce medication errors related to omissions, duplications and interactions. Hospitals continue to struggle to implement successful programmes that meet these objectives. Methods: The authors used improvement methods and reliability principles to develop and implement a process for medication reconciliation completion at admission at a large, paediatric medical centre. Medication reconciliation was defined as recording a complete and accurate list of each patient's medications within 20 min of admission by the nurse and reconciliation of those medications within 24 h of admission by the physician. Interventions focused on five main areas: leadership and support from senior physicians and nurses to sustain a culture of safety; simplification and standardisation of the electronic medication reconciliation application; clarifying roles and responsibilities; creating a highly reliable and visible system; and sustainability. Results: At baseline, only 62% of patients had their medications reconciled within 24 h of admission. Over a 9-month period, ≥90% medication reconciliation was achieved within 24 h of admission. These results have been sustained for 27 months. Conclusions: Through the use of improvement methods and reliability science, a sustainable process for medical reconciliation completion at admission was successfully achieved at a large, busy academic children's hospital.